Work design in future industrial production: Transforming towards cyber-physical systems. (January 2020) - Waschull, S.; Bokhorst, J.A.C.; Molleman, E.; Wortmann, J.C.
Highlights: Cyber-physical systems will significantly impact jobs in industrial production. Industrial jobs will increase in job complexity, skill variety and job autonomy. Simple and medium-skilled jobs will largely be substituted. Management choice determines work design, but is restricted by technology. Abstract: Rapid advancements in an array of digital technologies and applications promote the transformation of industrial production into cyber-physical systems (CPS). This process is projected to lead to a completely new level of process automation, thereby redefining the role of humans and altering current work designs in yet unknown ways. However, existing literature is rather ambiguous and not explicit on how the transformation towards CPS affects work design. In this study, we therefore consider this transformation at a much more detailed level. Our main contribution is the development of a framework to assess work design changes in the transformation towards CPS, and the consideration of the role of management choice therein. The framework relates (future) capabilities of CPS on the machine, production line, factory and supply chain scope to functions of human information processing. We then evaluate how the potential automation or augmentation of those functions by CPS affects job characteristics. Automation in this context is defined as the transfer of control and decision-making from humans to CPS, while augmentation means that technology is used to enhance human productivity or capability. We expect that the transformation towards CPS and the resulting automation and augmentation of tasks will shift the majority of human work to jobs characterized by high levels of job complexity, job autonomy and skill variety. This effect will become more severe when tasks are increasingly automated in the transformation towards CPS. During this development, human skills and knowledge will presumably remain critical in near future industrial production. Nevertheless, the ultimate implications for work design are strongly dependent on management choice. Strategic decisions are required on (1) which functions to automate across different scopes of operations and (2) how to group the resulting pool of tasks into jobs. This may result in various work designs. However, this choice is to a certain degree limited, and the role of technology is to restrict, rather than determine management choice.